Analysis of Calcium Oxalate Content and Stomata Amaranth Leaves (Amaranthus tricolor var. Giti Red) as Response to Drought Stress - Imam Safir Alwan Nurza; Chika Shafa Maura (Jurnal Penelitian Pendidikan IPA, 2024)
Amaranth is a plant that has calcium oxalate content in leaves. One of the roles calcium oxalate in plants is to increase drought tolerance. In addition, amaranth leaves also have anomocytic stomata. Stomata plant leaves are known to be formed genetically and not affected morphoanatomically under drought stress conditions, except density and conductance. Therefore, the research aimed to find out how the response of calcium oxalate levels and stomata of amaranth leaves (Amaranthus tricolor var. Red Giti) under drought stress. The research method used was a randomized block design (RBD) with two treatments, which are watering every day (WD) and watering at 50% wilting (SD) by observing stomatal density (stomata/mm2) and calcium oxalate content (%). Data were analyzed statistically with independent T-test and chi-square. The results showed that stomatal density and calcium oxalate content were affected by drought stress with a significantly decreased response. This indicates that the amaranth plant may become a plant that is resistant to drought stress by decreasing stomatal density and calcium oxalate levels.